Šiuolaikinės chemijos ir cheminės technologijos informavimo sistemos - Varnienė, Regina (Knygotyra, 1981)
According to the absolute volume of the amassed scientific information as well as to the rate of its growth chemistry has long been one of the first among other natural sciences. The increasing difficulties in the scientific-informational exchange in chemistry led to the formation of an effective informational system based on traditional forms of the dissemination and search of information by means of books and journals. This system was successfully expanding without any essential reconstruction of its traditional basis and existed in the course of a whole century up to the fifties of the 20-th century. In the mid-fifties and early sixties in addition to reference journals and other informational editions there appeared a great number of new specialized informational publications many of which are being nowadays computerproduced. Alongside with the formation and automatic publication of various informational edittions intensive research work in the origination of automatic informational systems is being carried out. Such world-known chemical informational centres as CAS Service and VINITI are engaged in particularly perspective and largescale researches in the creation of integrated informational systems. Of great interest to chemists is the integrated system “Assistant” and, specifically, its subsystem “Chemical Information” which is now being worked out in VINITI. As the results of the investigation of informational interests electrochemists has schown selective dissemination of information is now the mast prominent among other numerous kinds of information service. In the nearest future SDI will be introduced into the Institute of Chemistry and Chemical Technology of the Academy of Sciences of the Lithuanian SSR.